1997
DOI: 10.1212/wnl.48.3.741
|View full text |Cite
|
Sign up to set email alerts
|

The beta APP717 Alzheimer mutation increases the percentage of plasma amyloid-beta protein ending at A beta 42(43)

Abstract: We measured plasma levels of amyloid beta protein (A beta) ending at positions 40 (A beta40) and 42(43) [A beta42(43)] in six carriers of beta APP717 (Val to Ile) mutation linked to familial Alzheimer's disease (FAD) as well as in patients with sporadic AD (sAD) and controls. The percentage and the level of A beta42(43) were significantly higher in carriers of beta APP717 mutation relative to sAD, whereas A beta40 levels were decreased. In contrast, A beta levels and ratios were at similar levels in sAD, regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 6 publications
1
66
1
3
Order By: Relevance
“…Purified A␤40 (Bachem, King of Prussia, PA) was used as standard. The sensitivity of this ELISA assay is 1 pM A␤, and it is not affected by serum and plasma proteins because of the high affinity of the antibodies (Scheuner et al, 1996;Kosaka et al, 1997;Fukumoto et al, 2003). Cells were checked for consistent expression of constructs using Western blotting as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Purified A␤40 (Bachem, King of Prussia, PA) was used as standard. The sensitivity of this ELISA assay is 1 pM A␤, and it is not affected by serum and plasma proteins because of the high affinity of the antibodies (Scheuner et al, 1996;Kosaka et al, 1997;Fukumoto et al, 2003). Cells were checked for consistent expression of constructs using Western blotting as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Several genes that are involved in Aβ generation have been identified [9,21]. Mutations in APP and in Presenilins 1 and 2 and the presence of the apolipoprotein E (APOE) ε4 allele are associated with increased accumulation of Aβ in the brain and increased risk for AD [10,12,16], yet the mechanisms through which the genetic variants act are still uncertain. …”
mentioning
confidence: 99%
“…[13][14][15]21,22 Although one study showed an increase in Aβ levels, 22 the majority of studies have found no significant differences between AD and control cases. 13,14,16,17,23 Increased Aβ40 and sometimes Aβ42 correlate strongly with age. 15,23 A broad overlap in plasma Aβ levels between AD and control cases suggests that plasma Aβ cannot reliably differentiate sporadic AD from control cases.…”
Section: Blood Biomarkers For Alzheimer's Disease Blood Biomarkers Fomentioning
confidence: 99%
“…The plasma total Aβ or Aβ42 was increased in familial AD with presenilin or APP mutations 16,17 and in Down's syndrome with APP triplication, 18 which raises the possibility that sporadic AD may also be associated with detectable and diagnostic changes in Aβ plasma levels. Animal models suggest that Aβ can pass between cerebrospinal fluid (CSF) and plasma compartments, 19,20 but this has yet to be confirmed in humans.…”
Section: Amyloid β-Proteinmentioning
confidence: 99%